2015
DOI: 10.1016/j.jvs.2015.04.397
|View full text |Cite
|
Sign up to set email alerts
|

The effect of demographic factors and lesion severity on iliac stent patency

Abstract: In our experience with a large number of iliac interventions, younger age, non-Caucasian race, and EIA occlusion were strong predictors for loss of PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As noted in the literature, anatomic characteristics may be related to crossing approaches. Severe calcification, thrombosis, and rigid plaques are hindrances for the advancement of guidewires in the true lumen [10,11]. Statistically, we found that longer lesions with severe TASC categories were more likely to be crossed with the antegrade approach.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As noted in the literature, anatomic characteristics may be related to crossing approaches. Severe calcification, thrombosis, and rigid plaques are hindrances for the advancement of guidewires in the true lumen [10,11]. Statistically, we found that longer lesions with severe TASC categories were more likely to be crossed with the antegrade approach.…”
Section: Discussionmentioning
confidence: 69%
“…According to the TASC II guidelines, open surgery remains the gold standard of treatment for complex aortoiliac disease because it has excellent short- and long-term patency rates, which are as high as 85–92% [ 11 , 16 , 17 ]. The primary 2-year patency rate for complex and extensive lesions treated with endovascular procedures was 94% in one multicenter study, which is comparable to the outcomes of TASC A and B lesions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the literature, anatomic characteristics may be related to crossing approaches. Severe calci cation, thrombosis, and rigid plaques are hindrances for the advancement of guidewires in the true lumen [10,11]. Statistically, we found that longer lesions with severe TASC categories were more likely to be crossed with the antegrade approach.…”
Section: Discussionmentioning
confidence: 71%
“…According to the TASC II guidelines, open surgery remains the gold standard of treatment for complex aortoiliac disease because it has excellent short-and long-term patency rates, which are as high as 85%-92% [11,16,17]. The primary 2-year patency rate for complex and extensive lesions treated with endovascular procedures was 94% in one multicenter study, which is comparable to the outcomes of TASC A and B lesions [18].…”
Section: Discussionmentioning
confidence: 85%
“…Younger patients who need aortoiliac intervention likely exhibit a more aggressive form of the disease, becoming symptomatic at an earlier age and being more prone to atherosclerotic disease process after treatment and subsequent patency loss. [23][24][25] Therefore, further investigation warranted on how atherosclerotic processes or other clinical variables may differ between younger and older populations.…”
Section: Discussionmentioning
confidence: 99%